2015
DOI: 10.3109/10837450.2015.1048552
|View full text |Cite
|
Sign up to set email alerts
|

Application of Design Expert for the investigation of capsaicin-loaded microemulsions for transdermal delivery

Abstract: Our previous study reported that the Design Expert® Software showed a beneficial role in the development of microemulsions (ME) for transdermal drug delivery. To fully confirm the reproducibility and the reliability of simultaneous optimal ME formulations, the optimal ME formulations predicted by the Design Expert® Software were experimentally formulated and verified for their skin permeability. Ternary phase diagrams were used to predict the optimal ME area, and the ME formulations selected from outside this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…16) DoE analysis utilizes a response surface methodology (RSM) to estimate the main effect, the interaction effect and the outline of the response surface; many studies have successfully utilized RSM. [16][17][18] The simplex lattice mixture design is one type of RSM design that is used when the response changes as a function of the relative proportions of the components. All components must be entered in the same units of measure and each run must sum to the same total.…”
mentioning
confidence: 99%
“…16) DoE analysis utilizes a response surface methodology (RSM) to estimate the main effect, the interaction effect and the outline of the response surface; many studies have successfully utilized RSM. [16][17][18] The simplex lattice mixture design is one type of RSM design that is used when the response changes as a function of the relative proportions of the components. All components must be entered in the same units of measure and each run must sum to the same total.…”
mentioning
confidence: 99%
“…Table 6 shows the variance analysis of the regression model. Design-Expert software was used to complete the multiple regression fitting analysis of the test data [18][19][20][21], and the quadratic multiple regression equation for the qualified rate of single-seed, missing rate, reply rate, and three factors were obtained as follows: In the regression equation for the qualified rate, the p values of X 1 X 3 and X 1 X 2 were all greater than 0.05, so their effects on the qualified rate of single-seed were not significant, while other items had significant effects on the qualified rate of single-seed. In the regression equation for the missing rate, the p values of the interaction terms X 1 X 3 and X 1 X 2 were all greater than 0.05, so their effects on the missing rate were not significant, while other items had significant or extremely significant effects on the missing rate.…”
Section: Quadratic Regression Orthogonal Rotation Combination Simulat...mentioning
confidence: 99%
“…The conductivity of two MEs (> 0.01 mS/cm) indicated that ME1 and ME2 were oil-in-water MEs. [22][23][24] However, the classification of microemulsion types by using conductivity may be unsuitable for non-ionic surfactants such as Tween 80, so it should be confirmed by other procedures, for example, the dye test method. The pH value was 4.5, which was near normal skin pH and indicated that the microemulsions would not cause skin irritation.…”
Section: Preparation and Characterization Of Sfeo Microemulsionsmentioning
confidence: 99%